[symbol of Greek letter Pi]otamikon : sinews of Acheloios : a comprehensive catalog of the bronze coinage of the man-faced bull, with essays on origin and identity - Molinari, Nicholas J.,; Sisci, Nicola, (Archaeopress, 2016)
This work, 'Potamikon', presents an investigation into the origin and identity of the man-faced bull, as well as a catalogue of coins.